Delayed frozen embryo transfer failed to improve live birth rate and neonatal outcomes in patients requiring whole embryo freezing - Yuxia He; Haiyan Zheng; Hongzi Du; Jianqiao Liu; Lei Li; Haiying Liu; Mingzhu Cao; Shiping Chen (BMC, 2020)
Abstract Background Controlled ovarian stimulation (COS) has a negative effect on the endometrial receptivity compared with natural menstrual cycle. Whether it's necessary to postpone the first frozen embryo transfer (FET) following a freeze-all strategy in order to avoid any residual effect on endometrial receptivity consequent to COS was inconclusive. Objective The purpose of this retrospective study was to explore whether the delayed FET improve the live birth rate and neonatal outcomes stratified by COS protocols after a freeze-all strategy. Methods A total of 4404 patients who underwent the first FET cycle were enrolled in this study between April 2014 to December 2017, and were divided into immediate (within the first menstrual cycle following withdrawal bleeding) or delayed FET (waiting for at least one menstrual cycle and the transferred embryos were cryopreserved for less than 6 months). Furthermore, each group was further divided into two subgroups according to COS protocols, and the pregnancy and neonatal outcomes were analyzed between the immediate and delayed FET following the same COS protocol. Results When FET cycles following the same COS protocol, there was no significant difference regarding the rates of live birth, implantation, clinical pregnancy, multiple pregnancy, early miscarriage, premature birth and stillbirth between immediate and delayed FET groups. Similarly, no significant differences were found for the mean gestational age, the mean birth weight, and rates of low birth weight and very low birth weight between the immediate and delayed FET groups. The sex ratio (male/female) and the congenital anomalies rate also did not differ significantly between the two FET groups stratified by COS protocols. Conclusion Regardless of COS protocols, FET could be performed immediately after a freeze-all strategy for delaying FET failed to improve reproductive and neonatal outcomes.